The environmental setting of Epipalaeolithic aggregation site Kharaneh IV - Jones, Matthew D.; Maher, Lisa A.; Macdonald, Danielle A.; Ryan, Conor; Rambeau, Claire; Black, Stuart; Richter, Tobias (Elsevier, 2016)
The archaeological site of Kharaneh IV in Jordan’s Azraq Basin, and its relatively near neighbour Jilat 6 show evidence of sustained occupation of substantial size through the Early to Middle Epipalaeolithic (c. 24,000 – 15,000 cal BP). Here we review the geomorphological evidence for the environmental setting in which Kharaneh IV was established. The on-site stratigraphy is clearly differentiated from surrounding sediments, marked visually as well as by higher magnetic susceptibility values. Dating and analysis of off-site sediments show that a significant wetland existed at the site prior to and during early site occupation (~ 23,000 – 19,000 BP). This may explain why such a substantial site existed at this location. This wetland dating to the Last Glacial Maximum also provides important information on the palaeoenvironments and potential palaeoclimatic scenarios for today’s 43 eastern Jordanian desert, from where such evidence is scarce.